Makna Simbolik Pada Tari Piring: Kajian Semiotika Dalam Tari Tradisional Minangkabau - Erlinda, Erlinda (Institut Seni Indonesia Padangpanjang, 2025)
Tari Piring (Plate Dance) is one of the intangible cultural heritages of the Minangkabau people that holds strong aesthetic and symbolic values. As a form of traditional artistic expression, every element in Tari Piring—from movement, plate props, costumes, to accompanying music—contains cultural signs that can be analyzed through the semiotic approach of Charles Sanders Peirce, which includes three main elements: icon, index, and symbol. This study aims to uncover the symbolic meanings embedded in Tari Piring using a descriptive qualitative method, with data collected through performance observation, interviews with Minangkabau dance artists, and literature review. The results show that the circular plate movement, for example, is not merely a performance technique but represents the values of caution and diligence in the agrarian life of Minangkabau society. The sound of the plates touching the dancer’s fingers or body acts as an index of the collective rhythm of labor. Meanwhile, the brightly colored costumes with traditional motifs symbolize pride in cultural identity. This study concludes that Tari Piring is not just an aesthetic performance, but a medium of cultural communication that reflects the social, spiritual, and historical values of the Minangkabau community. Understanding these symbolic meanings allows for a more comprehensive and meaningful preservation of Tari Piring across generations.